2016
DOI: 10.1007/s00464-016-4830-0
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy by transabdominal lateral approach: 20 years of experience

Abstract: Lesion diameter over 45 mm is the determinant parameter for guidance of patients to surgeons with more extensive experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 39 publications
12
47
0
Order By: Relevance
“…In our study we registered pre-operative data like ASA score, radiological features and hormonal tests. In literature age and ASA score were direct related to increased of length of hospital stay and postoperative complications [24]. Radiological features and tumor size appeared as a very important predictive parameter of outcome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study we registered pre-operative data like ASA score, radiological features and hormonal tests. In literature age and ASA score were direct related to increased of length of hospital stay and postoperative complications [24]. Radiological features and tumor size appeared as a very important predictive parameter of outcome.…”
Section: Discussionmentioning
confidence: 95%
“…According to Dindo-Clavien scale rate we considered medical or surgical complications with grade ≥ 2 for statistical analysis with no significant correlation between mean tumor size, histological type and postoperative outcome (p value > 0.05). Coste T. et al [24] reported that postoperative medical complications were mainly respiratory diseases and various infections.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach to adrenal gland includes laparotomy, combined thoraco-abdominal access, retroperitoneal posterior access, laparoscopy, and robotic surgery [ 86 ]. Since the first successfully laparoscopic adrenalectomy (LA) performed by Gagner in 1991 [ 28 ], the lateral trans-abdominal approach has become the most common therapeutic strategy for adrenal neoplasm [ 28 – 34 ]. LA is associated with lower postoperative pain, reduced ileus, shorter hospitalization, earlier return to work, and a better cosmetic result, guarantying a lower morbidity (5–20%) and mortality rate (below 0.5%) compared to open adrenalectomy [ 25 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first successfully laparoscopic adrenalectomy (LA) performed by Gagner in 1991 [ 28 ], the lateral trans-abdominal approach has become the most common therapeutic strategy for adrenal neoplasm [ 28 – 34 ]. LA is associated with lower postoperative pain, reduced ileus, shorter hospitalization, earlier return to work, and a better cosmetic result, guarantying a lower morbidity (5–20%) and mortality rate (below 0.5%) compared to open adrenalectomy [ 25 , 31 , 34 ]. In contrast, open adrenalectomy is associated with higher mortality (2–4%) and morbidity rates (bleeding, pulmonary and cardiac complications, pulmonary thromboembolism, and wound infections) and is reserved worldwide only for large tumors (diameter >6 cm) and primary malignancies, based on the radicality of resection, minor tumor local recurrence, and major survival [ 27 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation